2004
DOI: 10.1088/0953-2048/17/10/022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Yb addition in Bi2Sr2CaxY bxCu2Oypartial melted thick films

Abstract: To study the phase relations in the Bi-2212 and Yb 2 O 3 system, Bi 2 Sr 2 Ca 1−x Yb x Cu 2 O y thick films are prepared by partial melt processing via an intermediate reaction between Bi-2212 and Yb 2 O 3 . When Bi-2212 and Yb 2 O 3 are partially melted and then slowly cooled, solid solutions of Bi 2 Sr 2 Ca 1−x Yb x Cu 2 O y form by reactions between liquid and solid phases which contain Yb. Following these reactions, Ca is partially replaced in Bi-2212 matrix and participates in the formation of secondary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Figure 4 represents the variation of lattice parameter c/c 0 (c 0 is the lattice parameter of the undoped region of the sample) as a function of thickness of the sample, exposed to Au diffusion at 800, 750 and 700 • C for 10 h. The solid curve shows the calculated concentration profile of Au in Bi-2223. The experimental data of figure 4 fit well with the theoretical curve, calculated for D = 1.2 × 10 −8 cm 2 s −1 at 800 • C by using equation (6). The…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Figure 4 represents the variation of lattice parameter c/c 0 (c 0 is the lattice parameter of the undoped region of the sample) as a function of thickness of the sample, exposed to Au diffusion at 800, 750 and 700 • C for 10 h. The solid curve shows the calculated concentration profile of Au in Bi-2223. The experimental data of figure 4 fit well with the theoretical curve, calculated for D = 1.2 × 10 −8 cm 2 s −1 at 800 • C by using equation (6). The…”
Section: Resultssupporting
confidence: 73%
“…There has been a tremendous amount of work on Bi(Pb)-Sr-Ca-Cu-O (BSCCO) system since its discovery. To improve the superconducting properties, partial substitution and diffusion have been investigated extensively [1][2][3][4][5][6][7][8][9]. Görür et al [10,11] investigated the effect of Ag diffusion on the properties of YBa 2 Cu 3 O 7−x (YBCO) thin films produced by electron-beam deposition techniques and bulk samples.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] It has been found that the Pb doping at Bi site in Bi-2212 increases the c-axis conductivity by more than one order of magnitude and reduces the anisotropy. The main advantages of Bi-based systems are their layered structure and hence texturing can be easily induced in it.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear if this compound acts as a dispersant or as a solvent. 12,13 The suspension stability depends not only on the dispersant but also on the solvent. Ethanol is the most common solvent chosen for different ceramic suspensions because it does not adversely affect the powder, dissolves most of the organic additives and has a very good balance considering different properties as drying rate, cost, dielectric constant or surface tension.…”
Section: Introductionmentioning
confidence: 99%